An Energy Efficient Architecture of IoT based on Service Oriented Architecture (SOA) - Maurya, Sudhanshu; Mukherjee, Kuntal (Informatica, 2019)
In present scenario, IoT is a platform where every day gadgets become smarter, each day processing will become shrewd, and every day verbal exchange becomes informative. Even as the IoT is still searching for its possess form, its results have already stared in making exquisite strides as a universal solution media for the associated situation. Study focused on architecture does always pave the conformation of associated discipline. The shortage of overall architectural abilities is at this time resisting the researchers to get by way of the scope of procedures based on energy efficient IoT. In this manuscript a Cloud Centric View of IoT Framework and an energy efficient architecture of IoT based on Service Oriented Architecture (SoA) with the algorithm has been proposed.